Analisis Semantik Kata Dla‘īf dalam Surah An-Nisa Ayat 28 dan Surah Ar-Rum Ayat 54 - Karunia Kholifah Dini Agustin (Alsina : Journal of Arabic Studies, 2020)
God created human beings along with their diverse traits and characters which have pivotal roles in driving them to do self-reflection to become better human beings blessed by God. In the Qur'an, Allah not only described the good characters and personalities that humans had, but also the bad ones hated by Him. The purpose of this research was to further reveal the meaning of Annisa verse 28 and Ar-rum verse 54 to avoid any mistakes in the interpretation of word dla‘īf located in different surah. This type of research was descriptive qualitative with literature review data collection techniques. Data analysis was conducted by reducing data, presenting it and drawing conclusions. From the results of this study, it was found that in the Qur'an there were many terms or words that were the same but had different meanings as was the case with the word dla‘īf in Annisa verse 28 and Ar-rum verse 54. In Surah Annisa the word dla‘īf was interpreted as a mental sate of faint-hearted person, whereas in surah Ar-rum was interpreted as a human weakness in terms of both physical and non-physical condition. The absence of balance in humans’ life can drive them to behave badly.